Emergency personnel neuroticism, health and lifestyle: A UK Biobank study. (17th January 2020) - Mutambudzi, M; Flowers, P; Demou, E
Abstract: Background: Emergency personnel face unpredictable and challenging incidents and their resilience and ability to cope influences their well-being. Personality traits, such as neuroticism, are postulated to be robust predictors of health and health behaviours. Despite evidence in the general population that neuroticism can positively impact health and health behaviours; to date neuroticism in emergency personnel has primarily been associated with adverse health outcomes. Aims: To assess whether neuroticism has a negative or positive impact on subjective and objective health and health behaviours in emergency personnel. Methods: This study used cross-sectional UK Biobank baseline data of emergency personnel (police, firemen and paramedics). Logistic regression models examined the strength of the associations of neuroticism tertiles with subjective (self-reported overall health and chronic conditions) and objective health (abdominal obesity) and self-reported smoking, sleeping, alcohol use and exercise levels. Results: High neuroticism was positively associated with poorer subjective health outcomes in all emergency personnel ( n = 2483). The association between neuroticism and chronic disease/s was significant for police in the second (odds ratio [OR] = 1.93, 95% confidence interval [CI] = 1.15–1.94) and third (OR = 1.62, 95% CI = 1.21–2.16) neuroticism tertiles. Neuroticism in firemen was associated with reduced abdominal obesity (OR = 0.49, 95% CI = 0.25–0.96) and increased exercise (OR = 2.14, 95% CI = 1.07–4.25). Conclusions: We observed positive and negative associations between neuroticism and health outcomes and behaviours. While differences were observed across the emergency personnel groups, more research is needed to better understand how personality traits may impact health in workers with physically and mentally intense jobs.